Analysis of mental models at criminal investigation division of the Indonesian National Police - Dadang Hartanto, (Technium Social Sciences Journal, 2020)
Mental models can function positively in organizations if they are managed well. The management of mental models is carried out from the surfacing step, to testing, to improving the internal picture of how the world works. This type of research is descriptive qualitative research. To obtain data used in-depth interview research techniques, observation, and documentation. While the data analysis mechanism is done by data reduction and data presentation. Based on the results of research that Bareskrim is able to live and adapt between various forces and interests because of mental models. priorities supported by understanding in seeing reality (personal mastery practice) can precisely determine positions and actions that are favorable for the existence of the organization. Harmonization of the relationship between senior-junior mental models and hierarchies will strengthen individual relationships because when harmonization occurs, conflicts can be avoided and group stability occurs due to compliance with the institutions that are mutually understood (common institutions) governing senior-junior and senior relations. hierarchy either in the form of ethics or norms, written or unwritten